Patient safety culture: Barriers and facilitators in high- and low-income countries. A Scoping review - Fonseca, Yanni Raúl; Ramírez Useche, Valeria; Vergara Ducuara, Jeny Katherine; Pérez Remuy, Koraima; Tapiero Rojas, Johan David (Horizonte Sanitario, 2026)
Objective: To describe the opportunities and challenges of incorporating precursor actions to a patient safety culture identified in high- and low-income countries. Materials and methods: A scoping review of the evidence was conducted to map and identify the characteristics of patient safety culture implementation in high-income countries compared to low-income countries. The PRISMA-ScR database was used as the source of evidence; Rayyan AI software was used for screening. The databases searched were Cochrane, Web of Science, Scopus, EBSCO, and PubMed. Results: The PRISMA-ScR report initially retrieved 1,053 records and concluded with 80 articles. The characterization of the countries showed that 62.5% were classified as high-income, compared to 37.5% classified as low-income. Conclusions: It was concluded that the HSOPSC survey is the most widely used tool in the process of diagnosing patient safety culture. Developed countries implement ongoing training and education programs, and team management skills strengthen the patient safety culture. Developing countries consider the lack of financial support a negative factor, leading to difficulties in implementation and development. Implementing models such as the second victim model, review systems, event reporting, and the use of a notification system facilitates the identification and generation of opportunities for the healthcare team. Key words: Quality of Health Care; Patient safety; Safety Management; Incident Reporting; Organizational Culture.